Parada gwiazd. (Gdynia : [s.n.], 1946)
Afisz inf. o występach artystycznych m.in. Hanna Brzezińska, Karol Hanusz, Wacław Jankowski.
Keywords: Brzezińska, Hanna -- (1909-1998).; Muzyka jazzowa -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Życie artystyczne -- Polska -- Sopot -- 1945-1970 -- druki ulotne; Sopot (Polska) -- 1945-1970 -- druki ulotne